P1-S6.13 A new approach to encourage HIV testing in high-risk populations at the Clinique l'Actuel. (10th July 2011) - Thomas, R; Machouf, N; Trottier, B; Vezina, S; O'Brien, R; Milne, M; Lavoie, S; Longpré, D; Huchet, E; Nguyen, V K
Abstract : Background: In Québec it is estimated that 1/3 of those infected do not know their HIV status, that HIV is diagnosed late in 41%, and that sex during primary infection is an important driver of the epidemic. In late 2008 Clinique l'Actuel launched a testing campaign tailored to MSM in Montréal using free rapid tests with the goal of increasing early diagnosis of HIV. In this study we evaluated the feasibility of and potential impact of facilitated access to rapid HIV-testing. Methods: Rapid HIV-tests offered through dedicated clinics were widely advertised in Montréal's MSM community. Patients calling for testing deemed at high risk were given appointments within 2 weeks, where they filled out a short questionnaire, received medical consultation routine STI screening, pre- and post-test counselling and their HIV test results within the hour. Ongoing support, care, and treatment were offered to those testing positive. Results: Over 9 months 2500 received HIV testing. 98% were men and median age was 34 (IQR=26–41). Of these patients, 42% were new to the clinic, 10% had never been tested previously, and 29% had not been tested within the past 2 years. 93% reported they were more likely to undergo repeat screening because of rapid testing. 2% were found to be HIV positive. Of these, 60% cited the rapid test as the primary reason for undergoing screening. 33% of those testing positive were in primary infection, as compared to 18% the previous year at Clinique l'Actuel (p=0.062) and 11% in Québec. Conclusion: Facilitated access to rapid HIV testing can increase uptake in high-risk patients. This may increase early HIV diagnosis and intervention to decrease transmission.